Respuesta :
Answers:
- a = 7x
- b = 3
==========================================================
Explanation:
Match up (7x+3)(7x-3) with (a+b)(a-b)
We have
- (7x+3) pair up with (a+b)
- (7x-3) pair up with (a-b)
We can see that a = 7x and b = 3
Furthermore, we can say,
(a+b)(a-b) = a^2 - b^2
(7x+3)(7x-3) = (7x)^2 - (3)^2
(7x+3)(7x-3) = 49x^2 - 9
The values of a and b are 7x and 3 respectively
(7x+3) (7x−3)
Using the format
Factorisation
(a + b)(a − b) = a² − b²
Therefore,
a = 7x
b = 3
Therefore,
From (a + b)(a − b) = a² − b²
(7x+3) (7x−3) = (7x)² - 3²
(7x+3) (7x−3) = 49x² - 9
learn more on factorisation here: https://brainly.com/question/22190900